Measurement and analysis of factors affecting financial Equilibrium An analytical study in a sample of commercial banks registered on the Amman Stock Exchange (2000-2021) - Yousef, Rawaa Ahmad (Journal of Economic, Administrative and Legal Sciences, 2024)
The research aims to test the factors (variables) that have the ability to achieve financial Equilibrium more than other factors in commercial banks, using a sample of (12) commercial banks listed on the Amman Stock Exchange for the period from (2000-2021). Financial indicators were chosen to measure the financial Equilibrium, namely (credit capacity, profitability index, liquidity index, capital adequacy index and financial flexibility index) and using the descriptive and analytical approach to the data and information contained in the financial statements of the banks under study. The factor analysis method and (spss) was also used to test the hypothesis and answer the question related to the study problem and reach the goals. The research also reached a set of results, The results of the analysis showed the validity of the hypothesis that there is a group of factors that affect the ability of the banks studied to achieve financial Equilibrium, as it became clear that there is a difference in the impact of financial Equilibrium indicators on the financial position of the banks., and the research presented a set of recommendations, the most important of which are The necessity for banks to diversify their lending portfolio and avoid credit concentration problems that affect the financial Equilibrium of banks in the event of an increase in non-performing loans.